2020
DOI: 10.1177/1075547020962107
|View full text |Cite
|
Sign up to set email alerts
|

Public Engagement With Science Among Religious Minorities: Lessons From COVID-19

Abstract: While scholars have highlighted how science communication reifies forms of structural inequality, especially race and gender, we examine the challenges science communication pose for religious minorities. Drawing on the disproportionate magnitude of COVID-19-related morbidity on Israel’s Ultra-Orthodox Jews, we examined their processes of COVID-19 health decision making. Survey results show that both religious and health-related justifications were common for personal decisions, yet a disparity was found betwe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
49
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 39 publications
(52 citation statements)
references
References 59 publications
3
49
0
Order By: Relevance
“…Although research has been done on how lay people interpret mathematical information when faced with a personal health hazard or decisions (e.g., Ancker & Kaufman, 2007 ), rarely have studies examined mathematical media literacy. Our findings do connect, however, to research on the scientific aspects of public engagement with COVID-19, which found correlations of science knowledge (operationalized as level of science education achieved in school/university) and understanding the science underlying COVID-19 (Baram-Tsabari et al, 2021 ; Taragin-Zeller et al, 2020 ).…”
Section: Discussionsupporting
confidence: 53%
“…Although research has been done on how lay people interpret mathematical information when faced with a personal health hazard or decisions (e.g., Ancker & Kaufman, 2007 ), rarely have studies examined mathematical media literacy. Our findings do connect, however, to research on the scientific aspects of public engagement with COVID-19, which found correlations of science knowledge (operationalized as level of science education achieved in school/university) and understanding the science underlying COVID-19 (Baram-Tsabari et al, 2021 ; Taragin-Zeller et al, 2020 ).…”
Section: Discussionsupporting
confidence: 53%
“…This is a common challenge in minority group research in Israel, and many studies report using samples that are only partially representative of the groups they are investigating. 65,72,125 As a result, our findings should be treated with caution as they do not necessarily represent older minority group members who are less cooperative when approached to take part in research in general and online studies in particular. Second, it should be stressed that this study measured compliance intentions to a particular and a simulated newly issued health instruction.…”
Section: Discussionmentioning
confidence: 95%
“…Increased science capital is beneficial as it empowers individuals to engage with science, importantly that which is relevant to society [ 10 , 11 ]. The necessity for the public to be engaged in science, have trust in science and understand the scientific process has been exemplified throughout the COVID-19 pandemic [ 59 , 60 , 61 ]. Within the events described here the participants perceived themselves to have increased their knowledge, and thus it is tempting to speculate we have increased the science capital of an adult cohort, some of whom may not have specifically sought it out, this was supported by the focus group analysis.…”
Section: Discussionmentioning
confidence: 99%